Leadership lessons from the Cherokee Nation : learn from all I observe - Smith, Chadwick Corntassel (McGraw Hill-Ascent Audio, 2014)
"If you want to be successful, it is this simple. Know what you are doing, love what you are doing. And believe in what you are doing." -- Will Rogers When Chad Smith became Principal Chief, the Cherokee Nation was a chaotic and dysfunctional entity. By the end of his tenure, 12 years later, the Nation had grown its assets from $150 million to $1.2 billion, increased business profits 2,000 percent, created 6,000 jobs, and dramatically advanced its education, language, and cultural preservation programs. How could one team influence such vast positive change? The Cherokee Nation's dramatic transformation was the result of Smith's principle-based leadership approach and his unique "Point A to Point B model"--the simple but profound idea that the more you focus on the final goal, the more you will accomplish . . . and the more you will learn along the way. In other words, "look at the end rather than getting caught up in tanglefoot." In Leadership Lessons from the Cherokee Nation, Smith combines Cherokee wisdom handed down from generation to generation with a smart leadership approach that takes today's very real issues into consideration. He explains why this leadership approach works and how you can apply it to your own organization, whether business, government, or nonprofit. Learn all the lessons that drive powerful leadership, including how to: Be a lifelong learner Solve problems with creativity and innovation Recruit and develop strong leaders Delegate wisely Act with integrity and dignity Don't be distracted from your objective Lead by example More than a simple how-to leadership guide, Leadership Lessons from the Cherokee Nation offers a holistic approach to the subject--how to become a powerful leader inside and direct your energy outward to accomplish any goal you set your mind to.